Հակոբ Սրճեցու ճառերի հայերեն թարգմանությունները - Հիլկենս, Էնդի (Մատենադարան)
We have only begun to scratch the surface of the Cilician Armenian translation movement, especially in the case of translations from Syriac texts.77 Even the Armenian reception of authors as highly appreciated as Ephrem and Jacob has received relatively little attention in non-Armenian scholarly circles, aside from a few rare exceptions. An investigation into the manuscript evidence is promising for the future of Syro-Armenian studies. It demonstrates a great interest in Jacob and his writings among the Armenians, starting in the twelfth century at the latest, all the way until the nineteenth century, when manuscripts with translations of Jacob’s homilies were still being copied. Furthermore, a particularly important step in the Armenian reception of Jacob was the integration of a Life of Jacob into the Armenian synaxarion by Gregory of Khlat around the turn of the fifteenth century. Изучение армянского переводческого движения киликийского периода, в особенности в области переводов сирийских текстов, лишь только начинается. Даже армянская рецепция таких высоко чтимых авторов, как Ефрем Сирин или Иаков Серугский, за незначительными исключениями, привлекала сравнительно мало внимания в неарменоведческих научных кругах. Изучение рукописных свидетельств убеждает в большом интересе армян к Иакову и его трудам: он начинается самое позднее с XII в. и не затухает вплоть до XIX в., когда все еще переписывались рукописи с переводами речей Иакова. Особенно важным шагом в армянской рецепции Иакова было включение жития Иакова в армянский синаксарий Григория Хлатского в самом начале XV века.
Keywords: Հայկական թարգմանական մատենագրություն; Ասորական գրականություն